Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Balai Taman Nasional Rawa Aopa Watumohai - Aris Aris; Abd. Azis Muthalib; Indira Yuana; Muh. Nur (Journal of Mandalika Social Science, 2026)
This study aims to determine the effect of work environment, work discipline, and work motivation on employee performance at the Office of Rawa Aopa Watumohai National Park. This research is a quantitative study with an explanatory research design. The population in this study consists of all employees, totaling 77 individuals, all of whom were selected as respondents. The data analysis method employed in this study is multiple linear regression analysis, processed using SPSS. The research findings reveal that: (1) the work environment, work discipline, and work motivation simultaneously have a significant effect on employee performance; (2) the work environment has a positive but insignificant effect on employee performance; (3) work discipline has a positive and significant effect on employee performance; and (4) work motivation has a positive and significant effect on employee performance at the Office of Rawa Aopa Watumohai National Park.